Nomad nirvana: key drivers of digital nomad satisfaction in Bukit Bintang hotels, Kuala Lumpur - Sapuan, Muhammad Afiq; Mohd Razali, Muhammad Amirul Haziq; Ariffin, Hashim Fadzil; Harun, Nor Hidayah (GADING Journal for the Social Sciences, 2024)
The global rise of digital nomads has reshaped traditional work environments, merging travel, leisure, and employment. Despite the growing presence of digital nomads in urban centres like Bukit Bintang and Kuala Lumpur, more research needs to be done to address how specific hotel features influence their satisfaction. This study aims to fill this gap by investigating the impact of internet connectivity, location, pricing models, and accommodation packages on digital nomad satisfaction with hotels in this region. Using a quantitative approach, data was collected from 278 digital nomads through purposive sampling. A comprehensive Google Forms questionnaire, employing Likert scales, was used to gather insights, and the data was analysed using regression analysis to identify key predictors of satisfaction. The findings reveal that internet connectivity and location are the most significant factors influencing digital nomad satisfaction, followed by pricing models and accommodation packages. These results provide valuable insights for hotel managers seeking to attract and retain digital nomads, emphasising the need for robust internet services and strategically located accommodations. This study contributes to practical and theoretical understandings of digital nomadism, offering actionable recommendations for enhancing hotel services and expanding the knowledge base on this emerging workforce.